2023
DOI: 10.1007/s11665-023-07800-0
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior of EN30B Forged Steels in the Presence of Non-metallic Inclusions

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ca treatment is widely used in steels. [54] Zhang [55] reported that the role of Ca treatment in MnS was correlated to both S and O contents in the steel.…”
Section: Calcium (Ca)mentioning
confidence: 99%
“…Ca treatment is widely used in steels. [54] Zhang [55] reported that the role of Ca treatment in MnS was correlated to both S and O contents in the steel.…”
Section: Calcium (Ca)mentioning
confidence: 99%